EFFECT OF SCIENCE ANXIETY ON STUDENT’S ENGAGEMENT IN PHYSICS LABORATORY EXPERIMENT: A STUDY OF SENIOR SECONDARY SCHOOL STUDENTS IN ENUGU STATE, NIGERIA - Odo, Livinus O. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
A physics laboratory experiment is an essential component of science learning that positively establishes scientific attitudes and skills in young learners. However, insinuation suggests that most students show less commitment to engaging in a physics lab experiment. Thus, the purpose of the present study was to examine science anxiety as a factor that could predict the variation in students' participation in a physics lab experiment. Two hundred and eleven students who met the inclusion criteria were selected from secondary schools in the Enugu state as the participants. The respondents completed a self-report measure of science anxiety and engagement in a lab experiment questionnaire. The linear regression established a statistically significant effect of science anxiety on the respondent's participation in physics lab experiments at F (1,209), 214.518 P< .05 with adjusted R2 indicating that science anxiety contributed about 31.1% of the variance in student engagement in a physics lab experiment. Thus, the study concluded that science anxiety positively determines students' participation in a lab experiment.